Migration and focusing of porphyry deposit-forming fluids through aplitic mush of the Saginaw Hill cupola, Arizona, United States - Carter, Lawrence C.; Williamson, Ben J. (Frontiers in Earth Science, 2024)
Porphyry-type Cu(-Au-Mo) deposits form in the upper (ca. 2-5 km deep) parts of large, longlived magmatic-hydrothermal systems in which mineralising fluids are thought to be derived from mid-to shallow-crustal magma chambers. Increasingly, however, magmatic systems are viewed as consisting of mush with minor and transient lenses of magma, with mush being a variably packed framework of crystals with interstitial melt and magmatic volatile phase (MVP).In this context, questions remain as to the source (mainly depth) and mechanisms of transport and focussing of the vast volumes of fluids required for shallow level porphyry-type mineralisation. Even more problematic is a paucity of first-order textural evidence for the presence of mush in magmatic-hydrothermal systems, including those which host porphyrytype deposits. To address this, we have studied the aplitic porphyry cupola of the Saginaw Hill magmatic system, Tuscon, Arizona, USA, where magmatic-hydrothermal features are exceptionally well exposed, including a massive silica cap, quartz unidirectional solidification textures (USTs), stockworks of multiple generations of variably mineralised quartz veins and mineralised miarolitic cavities. From field-to micro-scale textural and geochemical studies, particularly observations of vermiform quartz between earlier generations of magmatic quartz and feldspar, we evidence the development of fluid pathways through mush at the magmatichydrothermal transition. These are shown to connect and provide fluids and ore constituents to the mineralised miarolitic cavities and early quartz vein stockworks. We suggest that this process should be considered in all new genetic, exploration and numerical models for porphyry and similar types of magmatic-hydrothermal ore-deposits.